Faculty Experiences: Virtual versus Traditional Problem-based Learning during COVID-19 in a Saudi Medical College - Almansour, Mohammed; Alrumaihi, Nouf; Alanazi, Omar; Feda, Jude; Saeed, Majda; Soliman, Mona (Journal of Nature and Science of Medicine, 2024)
Abstract Background: The COVID-19 pandemic has forced a fast change to new teaching approaches based on online education. Problem-based learning (PBL) was one of the modified teaching strategies. The current study sought to examine faculty perceptions of virtual versus traditional PBL during the COVID-19 pandemic at a Saudi medical college. Methods: This is a retrospective cross-sectional study conducted at King Saud University's College of Medicine. We compared the perceptions of faculty members who facilitated traditional face-to-face PBL in 2019-2020 and virtual PBL in 2020-2021. An online survey with demographic and practice data was distributed. The faculty's perception of PBL facilitation, student learning, and overall satisfaction was investigated using a 5-degree Likert scale: 15 items grouped into three main areas. All of the questions were written in a way that compares traditional and virtual PBL. Mean scores were determined for all parts, and the findings were reported as mean standard deviation, with scores of 3 and above considered positive, and scores of <3 considered negative. The data were analyzed with SPSS version 25.0. Results: In the study period, 57 faculty members facilitating PBL replied to the survey (response rate 67.85%). There were no gender variations in the representation of participants (male 56.1%, female 43.9%), and they come from a variety of basic and clinical departments. The majority of participants (91.3%) have more than 2 years of PBL facilitation experience, and 64.2% have received training in both virtual and traditional PBL facilitation. The faculty assessment of facilitating virtual PBL was favorable as overall satisfaction, with the mean of the components in the satisfaction section being 3.67. In terms of facilitation preferences, we discovered that despite the amount of effort involved in facilitating traditional PBL sessions (mean = 3.47), their motivation to facilitate traditional PBL was higher than that of virtual PBL (mean = 3.33). Faculty perceptions of students' learning in PBL were more traditional, with the mean of the items in this section (such as students' motivation, participation, and group dynamics) being higher (3.616). Conclusions: The faculty's satisfaction with their abilities to properly facilitate virtual PBL sessions did not detract from their motivation to be in direct personal interaction with students during PBL sessions. To ensure faculty care about students' learning in virtual PBL, their perception had to be correlated to their learning outcomes.